Towards sustainable industrial development - A systems thinking-based approach (International Seven Journal of Multidisciplinary, 2024)
Various critical global issues, including global warming and poverty, have been recognized and identified by the United Nations (UN) as drivers for unsustainability. Consequently, the UN established the Sustainable Development Goals (SDGs) with the aim of seeking universal peace and larger freedom by balancing the three dimensions of sustainable development, i.e. economic, social and environmental. A particular attention SDGs pay is in eradicating poverty as this is considered one of the greatest global challenges. Poverty is not only an economic matter as it also has an impact on the social and environmental dimensions. A strategy to tackle poverty is to foster industry development. However, a holistic point of view is necessary by also considering stakeholders otherwise, it becomes a neoliberal solution. Despite the fact that some research has been conducted, e.g. case studies and surveys of sustainable practices, there is a lack of industrial sustainable development as a framework to tackle sustainability issues. Thus, this paper proposes a framework for industrial sustainable development under a socially inclusive approach within the context of the Mexican manufacturing industry. The framework proposal is based on a state-of-the-art literature review conducted in the Web of Science and Scopus databases.